2022
DOI: 10.1177/01455613221132115
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Indicators in Peripheral Blood in Sudden Sensorineural Hearing Loss Patients With Different Audiogram Shapes

Abstract: Objective: A retrospective study was conducted to explore the immune-inflammatory responses in sudden sensorineural hearing Loss (SSNHL) patients with different audiogram shapes. Methods: One hundred and ten inpatients with SSNHL were assigned to 4 subgroups according to the audiogram shape and treated with systemic methylprednisolone. The numbers of white blood cells, neutrophils, lymphocytes, platelets, and monocytes were counted. The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the rst study to examine the relationship between the SII and HL. Yuting Yao et al previously reported that the blood immune marker SII in patients with both low-frequency and high-frequency hearing loss was signi cantly greater than that in normal controls 19 . In addition, Xu Zhang et al reported that patients with sudden sensorineural hearing loss (SSNHL) exhibit in ammatory and immune responses in vivo, and the SII plays an important role in predicting the prognosis and guiding treatment of these patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, this is the rst study to examine the relationship between the SII and HL. Yuting Yao et al previously reported that the blood immune marker SII in patients with both low-frequency and high-frequency hearing loss was signi cantly greater than that in normal controls 19 . In addition, Xu Zhang et al reported that patients with sudden sensorineural hearing loss (SSNHL) exhibit in ammatory and immune responses in vivo, and the SII plays an important role in predicting the prognosis and guiding treatment of these patients.…”
Section: Discussionmentioning
confidence: 96%
“…The greater the SII is, the worse the therapeutic effect is for such patients 20 . Yuting Yao et al also showed that the immune and in ammatory response of the cochlea may be the common pathophysiology of all patients with SSNHL 19 . In this immune response, the presence of macrophages in the cochlea plays a very important role.…”
Section: Discussionmentioning
confidence: 99%
“…Elias et al studied plasma malondialdehyde (MDA) activity in patients with SSNHL from the perspective of oxidative stress and studied the role of MDA in the prognosis of sudden deafness (34). Yao et al studied inflammatory indexes in the peripheral blood of patients with SSNHL by using different audiogram shapes (35). Feng et al investigated serum albumin and bone turnover biomarkers as potential prognostic markers for SSNHL (36,37).…”
Section: Discussionmentioning
confidence: 99%